Nurses’ Experiences at the Intensive Care Unit for COVID-19 in Indonesia: A Study of Hermeneutic Phenomenology - Fitri Mailani; Emil Huriani; Boby Febri Krisdianto; Elvi Oktarina (Iranian Journal of Nursing and Midwifery Research)
Background: Nurses working in Intensive Care Unit (ICU) for COVID-19 are more at risk as they interact more with infected patients. Therefore, this study aimed to explore the experience of Indonesian nurses who work in ICU for COVID-19 patients. Materials and Methods: A qualitative hermeneutic phenomenological approach was used. A total of 20 nurses working in the respective ICUs of eight COVID-19 referral tertiary hospitals in Indonesia were recruited using purposive sampling. Semistructured individual video call interviews were conducted in June–September 2021; then, Diekelmann’s hermeneutic phenomenological approach was used to analyze and interpret the data. Results: Thirteen subthemes describing the following four themes, namely, the pleasing and bad feelings, new challenges of working, nursing professional growth, and nurse resource management for COVID-19 . Conclusions: This study describes nurses’ experiences working in ICUs during the COVID-19 crisis, such as their feelings, perceived challenges, and received support. Nurse leaders play a significant role in providing adequate Personal Protective Equipment (PPE), flexible work shifts, and a caring and healing work environment. However, being aware of the limit of pressure that an individual can manage and providing adequate allowance as rewards for work in risky areas are essential to avoid burnout.